1998
DOI: 10.1523/jneurosci.18-16-06254.1998
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of M-Type Potassium Current by Intracellular Nucleotide Phosphates

Abstract: The effects of intracellular application of various concentrations of adenine nucleoside phosphates and nucleotide analogs on the M-type K current (IM) of single neurons isolated from sympathetic ganglia were studied. With 1 mM MgATP intracellularly IM decreased to 25% of its initial level 39 min after the start of whole-cell recording. In the absence of ATP the current decreased more rapidly. Addition of glucose and pyruvate extracellularly was equivalent to adding 1 mM MgATP intracellularly. AMP-PNP, a nonhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Electrophysiological studies of these neurons have not yielded evidence of their expression either. However, KCNQ channels are very sensitive to disruption of the intracellular milieu, as might occur with conventional electrophysiological approaches (Simmons and Schneider, 1998). In our hands, whole-cell dialysis of medium spiny neurons led to the loss of KCNQ-like currents in minutes.…”
Section: Striatal Projection Neurons Express Kcnq Channel Mrna and Chmentioning
confidence: 51%
“…Electrophysiological studies of these neurons have not yielded evidence of their expression either. However, KCNQ channels are very sensitive to disruption of the intracellular milieu, as might occur with conventional electrophysiological approaches (Simmons and Schneider, 1998). In our hands, whole-cell dialysis of medium spiny neurons led to the loss of KCNQ-like currents in minutes.…”
Section: Striatal Projection Neurons Express Kcnq Channel Mrna and Chmentioning
confidence: 51%
“…In a subset of experiments, the pipette solution was added with calcium buffers, including 5 m m EGTA, 10 m m 1,2‐bis(2‐aminophenoxy)ethane‐ N , N , N ′, N ‐tetra‐acetic acid (BAPTA) or 10 m m EGTA with 8 m m Ca 2+ (140 n m free Ca 2+ ; MaxChelator, Stanford University). Although the pipette solution contained no ATP, the relatively high concentration of extracellular glucose was used to maintain intracellular ATP (Simmons & Schneider, 1998). The bath and pipette solutions for single‐channel recordings in oocytes were symmetrical and contained 100 m m sodium gluconate and 10 m m NaCl instead of 140 m m NaCl, and other components were the same as the Ca 2+ ‐free bath solution for HEK 293 cells.…”
Section: Methodsmentioning
confidence: 99%
“…The observation that the sustained depolarization was either absent or smaller in amplitude in open-tip whole-cell configuration may reflect the presence of a soluble intracellular messenger in the pathway causing inhibition of the M-channels (see Marrion, 1997). However, other studies have shown that the M-current is sensitive to the availability of hydrolysable ATP (Simmons & Schneider, 1998), or that these currents are not observed with opentip whole-cell configuration (Xu & Adams, 1992), so it is also possible that the disturbance of the intracellular milieu inherent to the open-tip patch recording technique may prevent the observation of the effects of histamine on the M-current.…”
Section: M-currents In Chromaffin Cellsmentioning
confidence: 99%